Intercultural Communication Under New Challenges. The 14th RISA Convention - D. S. Gorshenev (Концепт: философия, религия, культура, 2022)
MGIMO University started a new academic year with the 14th Russian International Studies Association (RISA) Convention. Held on October 13th–15th the Convention invited leading scholars to discuss historical, socio-economic, political, and legal aspects of shaping a new world order. Its traditional interdepartmental panel Intercultural Communication this year brought together speakers from Russia, Belarus, Moldova, Abkhazia, South Ossetia, Uruguay, and Iran to discuss cultural diversity under new challenges. An interdisciplinary array of 52 reports by philosophers, culturologists, linguists, political scientists, regionalists, religious scholars, art historians and specialists in the field of media studies presented a vivid picture of modern research in the sphere of intercultural communication. The reports and exchange of opinions encouraged scientists to investigate related academic fields and expand their theoretical horizons by getting acquainted with the achievements of interdisciplinary research in related fields of knowledge. Among the most discussed topics that aroused keen interest of the audience are the following: a new linguistic reality of intercultural interaction on the example of the evolution of the Spanish language, the preservation of the cultural heritage of peoples in the context of globalization, various ways of visualizing culture and their influence on the formation of regional and national identity, philosophical understanding the challenges facing traditional manifestations of culture and much more. The session demonstrated that intercultural communication lying at the intersection of multiple parties’ interests remains flexible and adaptable and the dialogue of cultures is a reciprocal and ever-important process.